2013
DOI: 10.1086/673464
|View full text |Cite
|
Sign up to set email alerts
|

Central Line–Associated Bloodstream Infection in Neonatal Intensive Care Units

Abstract: The increase in CLABSI rates in Quebec NICUs seems to be associated with an increased proportion of cases with underlying intra-abdominal and pulmonary pathologies, which needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 33 publications
(28 reference statements)
1
16
0
1
Order By: Relevance
“…The reported incidences of CLABSI in neonates admitted to NICUs vary from 0.8 to 18.1 per 1,000 catheter-days (3, 10, 1419). Variation in reported incidences is probably due to methodological differences between the studies including different cohort characteristics, but may also be attributable to differences in actions to prevent the development of CLABSI between the departments, such as emphasizing hand hygiene, avoidance of certain medications, and using bundles of care.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidences of CLABSI in neonates admitted to NICUs vary from 0.8 to 18.1 per 1,000 catheter-days (3, 10, 1419). Variation in reported incidences is probably due to methodological differences between the studies including different cohort characteristics, but may also be attributable to differences in actions to prevent the development of CLABSI between the departments, such as emphasizing hand hygiene, avoidance of certain medications, and using bundles of care.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the CLABSI rate by nearly 20% from a baseline rate of 1.333 would prevent ∼35 CLABSIs and save as many as 7 lives. 41 Based on published estimates of up to $69 000 attributable-cost per CLABSI, we could expect a cost-saving of up to $2.4 million. 6-11…”
Section: Figurementioning
confidence: 99%
“…8 Additionally, Blanchard et al's cohort study noted an association with underlying intra-abdominal pathology and that 51% of their CLABSI were due to coagulase-negative staphylococci and 11% due to Staphylococcus aureus. 9 In contrast, other studies have found predominantly gram-negative organisms in neonatal CLABSI. 10 Variations in risk factors and pathogens emphasize the need for each NICU to develop an individualized QI approach based on their population's characteristics.…”
Section: Defining the Problemmentioning
confidence: 91%